(untitled) (Research, Society and Development, 2018)
This work has the objective to describe tests about logical notions of volume and space on children’s speech during the Piagetians tests. The tests were applied in children aged 4 and 9 years old, re in order to evaluate the cognitive dimensions and the stages of development of the subjects studied. We handle materials such as: glass, water, jar, modeling clay and pencil. The results indicate the notions of children related to volume and length. Such dimensions are associated with the development of logical operations. In the Volume Conservation test, it can be observed that child A can not understand what was done, and is therefore preoperative. In the second test (Conservation of Length), it demonstrates inconsistency in its statement, easily yielding the conter argument, thus being at the intermediate level. Child B demonstrated volume and length preservation in the tests, explaining the answers correctly, and could be categorized as operative. Accordingly, the study concludes that assessing cognitive development contributes to the organization of pedagogical work.